Digital Entrepreneurship and Social Value Creation: Social Media as a Catalyst for Inclusive Innovation - Kumar, Dr. R. Ravi; Dr. Praveen B. M (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2026)
The rapid diffusion of social media platforms has reconfigured how entrepreneurs in emerging economies design, communicate, and scale innovative solutions to social problems. This conceptual paper examines digital entrepreneurship through the lens of social media–enabled value creation, aligning with the conference track on digital tools for social entrepreneurship and innovation for inclusive growth. Drawing on public relations, stakeholder engagement, and innovation diffusion theories, the paper proposes an integrated framework explaining how platform affordances (visibility, interactivity, and datafication) shape opportunity recognition, community building, and trust among diverse stakeholders. It argues that Facebook, Instagram, YouTube, and TikTok function not only as marketing channels but also as socio-technical spaces where co-creation, advocacy, and crowdfunding converge to accelerate social transformation. The framework further highlights generational differences in adoption patterns and participation logics, with Generations X, Y, and Z occupying distinct yet complementary roles as founders, collaborators, and prosumers. Special attention is given to resource-constrained start-ups and grassroots change-makers, for whom low-cost digital tools substitute for traditional advertising, lobbying, and infrastructure. The paper concludes with implications for policymakers, incubators, and NGOs on designing capacity-building programmes that leverage social media analytics, storytelling, and digital literacy to support sustainable entrepreneurial ecosystems. By theorising the relationship between digital platforms, entrepreneurship, and social change, the study offers an agenda for future empirical research in the Global South, particularly within Indian urban and semi-urban contexts.